2018
DOI: 10.5547/01956574.39.si1.call
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Development on Energy Intensity in China

Abstract: In this study, we analyse the relationship between financial development and energy intensity in 28 Chinese provinces over the period 1999 to 2014. Using a wide variety of financial development measures, as well as specific indicators capturing the level of state intervention in the financial system and the degree of market-driven financing in the economy, we examine whether limited access to finance acts as a barrier to reducing energy intensity. Our estimations control for variables such as state investment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Analyzing the association between financial advancements and energy intensity, Aller et al (2018) investigated the impact several measures of financial progress on energy intensity. Utilizing the panel data for twenty eight provinces of China between the years 1999 to 2004, the findings of the analysis suggested that low performance of financial sector bring enhancements in energy intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analyzing the association between financial advancements and energy intensity, Aller et al (2018) investigated the impact several measures of financial progress on energy intensity. Utilizing the panel data for twenty eight provinces of China between the years 1999 to 2004, the findings of the analysis suggested that low performance of financial sector bring enhancements in energy intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Essential productive factors involved in the existing fruitful studies include capital, labor, land, energy, etc. [12][13][14][15]. Although important findings have been made, there are few studies on energy misallocation.…”
Section: Introductionmentioning
confidence: 99%
“…The financing tools such as green bonds and climate bonds were introduced for funding environmentally beneficial initiatives (Tolliver et al 2020). As many academic writers have pointed out (Akomea-Frimpong et al 2021;Chang et al 2021;Pyka and Nocon 2021;Aller et al 2018;Baloch et al 2018;Bovari et al 2020;Lamperti et al 2021), however, the financial gap on green investment is still huge in amount.…”
Section: Literature Reviewmentioning
confidence: 99%